Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

To put this in context, this is my first day on working with group actions.

Let $G$ a group and $X$ a $G$-set. Let the group action of $G$ on $X$ be:

$G×X→X:(g,x)\mapsto g.x$

Show that $x∼y ⇔∃g∈G : g.x=y$ is a equivalence relation on $X$.

This is what I got:
Let $x∈X$, then $e.x=x$ by definition, therefore $x∼x$.
Let $x,y∈G$ and $x∼y$, then $∃g:g.x=y$....

Now I don't know what to do, I know the rule $g_1.(g_2.x)=(g_1 \circ g_2).x$. And I thought about using $λ_{g^{-1}}$ on both side, but my problem is that $g.x ∈X$ and not in the group $G$, so I don't know how I can deal with this.

share|cite|improve this question
up vote 2 down vote accepted

If $g\cdot x=y$, where $\cdot$ represents the action, then $g^{-1}\cdot(g\cdot x)=g^{-1}\cdot y$. Now use $(gg')\cdot x=g\cdot (g'\cdot x)$.

For transitivity, suppose $g\cdot x=y$ and $g'\cdot y =z$ and use $(gg')\cdot x=g\cdot (g'\cdot x)$ yet again.

You can equivalently show that the action of $G$ on $X$ partitions $X$ into $G$-orbits of the form $$Gx=\{gx:g\in G\}$$

for each $x\in X$, so that the partition gives rise to an equivalence relation.

share|cite|improve this answer
Aaaah thanks ! I see, so you use some kind of similar function as $λ_{g^{-1}} : G→G :h\mapsto g^{-1}\circ h $, but now in the form of: $G×X → X : (g^{-1},x) \mapsto g^{-1}.x$ Right ? – Kasper Mar 28 '13 at 0:07
@Kasper You needn't think about it in terms of functions. Just use the action of $G$ on $X$. You know you can perform $g^{-1}\cdot y$ for any $y\in X$. And in particular if $x\in X$ and $g\in G$, $y=g\cdot x\in X$. That's all there is to it. – Pedro Tamaroff Mar 28 '13 at 0:09
Cool, thanks ! Things are becoming to get clear ! – Kasper Mar 28 '13 at 0:12

If $g\cdot x=y$, then $x=g^{-1}\cdot (g \cdot x)=g^{-1}\cdot y$.

If $g\cdot x = y$ and $g'\cdot y = z$, then $(g'g)\cdot x = z$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.